Clinical presentation of paradoxical vocal fold motion or laryngeal dyskinesia in infants. (November 2022) - So, Raymond J.; Jenks, Carolyn; Yi, Julie; Ryan, Marisa A.; Tunkel, David E.; Walsh, Jonathan M.
Abstract: Objectives: Paradoxical vocal fold motion (PVFM) is not well-characterized in infants. Sex- and race/ethnicity-based differences have been described in older children with PVFM. This study's objectives are to characterize demographic and clinical characteristics of infants diagnosed with PVFM and investigate sex- and race-specific differences in presentation. Methods: We retrospectively reviewed infants ≤1 year of age diagnosed with PVFM at our institution from 2009 to 2019. Patient demographics, symptoms, and findings on flexible laryngoscopy are described. Sex- and race/ethnicity-based differences were assessed using Fisher's exact test analyses. Results: We identified 22 infants who were diagnosed with PVFM. The average age (range) at diagnosis was 5.7 (0.25–12.0) months, and 45.5% were male. The majority (54.6%) of patients identified as non-Hispanic White. Common comorbidities included GERD (45.5%) and chronic rhinitis (13.6%). Stridor was the only presenting symptom in the majority of patients (95.4%). The most common episode triggers were crying (45.5%), feeding (27.3%), and gastric reflux (9.1%). On flexible laryngoscopy, PVFM was observed in 95.5% of patients. A third of patients (31.8%) were misdiagnosed as having reactive airway disease or laryngomalacia prior to evaluation by otolaryngology. No sex- and race/ethnicity-based differences in presentation were identified. Conclusion: We present the largest case series of PVFM in infants. We found sparse clinical signs/symptoms other than stridor and a high incidence of misdiagnosis, which supports the importance of objective flexible laryngoscopy for the evaluation of stridor in this age group. Previously reported sex- and race/ethnicity-based differences in presentation of PVFM were not observed in this cohort of infants.